Pursuing a national health strategy in a decentralized fiscal regime - Esguerra, Emmanuel F. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1997)
Drawing from the public finance literature on expenditure assignment, this paper analyzes how devolution in the health sector is being operationalized in the Philippines. A central issue is how the central government can ensure that national and local objectives coincide. The pattern of health spending after devolution is described, and the financing of national health priorities at the local level through the Comprehensive Health Care Agreements is examined. The paper concludes by suggesting some guidelines for a financing mechanism for locally implemented health projects.